Placing Plastic Stent via Percutaneous Transhepatic Biliary Drainage following Failure of Endoscopic Retrograde Cholangiopancreatography: Review of Case Series - Santoso, Antonius Gunawan; Baskoro, Nurdopo; Beatrice, Novia Nathania; Edwina, Tanya; Budiono, Bernadus Parish (Digestive Disease Interventions, 2024)
The aim of this study is to describe the technical procedure, patency, and complications of percutaneous biliary plastic stent insertion following failure of the endoscopic approach. The data from 11 patients who underwent percutaneous plastic biliary stent placement following endoscopic approach failure between March 2022 and December 2023 were retrospectively evaluated. Stent placement was successful in all patients. Reduction of the total serum bilirubin level was achieved in all patients. No major complications occurred in all patients. A plastic stent provided enough drainage for patients with patency in our studies for up to 5 months.
Keywords: PTBD; plastic stent; biliary tract obstruction